Estudo do desenvolvimento humano no Bairro Resistência (Vitória-ES) - Ferreira, Deiwson Henrique Gomes (2008)
This work aimed to study the human development in the neighborhood Resistência belonging to the region of São Pedro in the city of Vitória-ES, based on the calculation of the Municipal Human Development Index (HDI-M) and Living Conditions Index (LCI). The latter is an extension of the Human Development Index (HDI), covering more information, that is, while the HDI comprises only three dimensions: health, education and income, embodied in four indicators, the LCI incorporates the addition of these children and housing, total of 18 indicators. This study is necessary to obtain information relating to living conditions of local people in order to help the local public policies. Since this calculation can be done periodically, serving as a diagnosis and evaluation of policies implemented, indicating the areas where the greatest failures occur, thus signaling the need for public interventions in these areas for improving the quality of life of the community. The methodology used in the research was based adopted by João Pinheiro Foundation (FJP) and the Institute of Applied Economic Research (IPEA) of 1998, since the HDI-M and LCI were created by these two bodies. Data were collected by the application of 317 questionnaires in a sample of homes of neighborhood Resistência, statistically defined. The main findings were: 1 - The HDI-M of neighborhood Resistência found himself in the range of medium human development (0.5 <HDI-M <0.8) resulting in the value LCI 0.769 and studied the region remained in the range of high human development, (LCI> 0.8), and more specifically the order of 0.813. 2 - The size and longevity income they remained in the category of medium human development, while the size education remained in the category of high human development for the HDI-M. Already the areas education and income were the worst results they obtained in the LCI, both located in the range of medium human development, the other areas were found to be in the range of high human development.